Liar, liar : the theory, practice, and destructive properties of deception - Paulsen, Gary (New York : Scholastic, 2011)
Fourteen-year-old Kevin is very good at lying and doing so makes life easier, but when he finds himself in big trouble with his friends, family, and teachers, he must find a way to end his lies forever.
Z
Companion book to: Vote, Crush, Family ties, and Flat broke.
940
Z
Keywords: Honesty -- Fiction; Interpersonal relations -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Family problems -- Fiction; Humorous stories